Thriving Together: a novel workshop to improve cohesion and class culture in medical school cohorts - Herod, Tyler; Henderson, Brett; Donovan, Matthew; Sahiti, Qëndresa; Ford, Zachary; McDermott, Emma (Canadian Medical Education Journal, 2024)
Implication Statement Thriving Together, a workshop for first year medical students, addresses crucial aspects of class culture early into medical school. Through small group discussions, this student-led event creates a safe space for open dialogue and self-reflection. Participants gain valuable insights into classmates’ perspectives and how to foster communication, empathy, and improved class cultures. These lessons are likely to transfer into future practice through enhanced conflict-resolution and relationship-building skills, contributing to higher-quality patient care. Because Thriving Together can readily be adopted elsewhere, we encourage other medical schools to conduct similar workshops to help in addressing an otherwise neglected aspect of medical education.